Profil Pemecahan Masalah Persamaan Linear Satu Variabel Siswa Climber Pada Kelas VII SMP Negeri 3 Palu - Padliani Padliani; Sudarman Bennu; Muh. Rizal (Universitas Tadulako, 2019)
This research aimed to describe the profil of students’ problem solving of one variable linear equations of the climber students’ in the grade VII of SMP Negeri 3 Palu. The research subject was gained by adversity response profile questionnaire to classify the type of student that type of adversity quotient climber, camper, and a quitter. Subjects used in this research only one student type of climber. The results of this research shows that: (1) understand the problem, students climber unyielding so as to identify and propose things that are known and questioned on the issue, (2) make a plan, students climber motivate yourself and not easily satisfied so as to propose a contingency plan that will be done to solve the problem, (3) carrying out the plan, students climber always trying and not give up so as to implement the plan as planned and the results obtained are correct, and (4) looking back, students climber is not so just believe in the truth of the results obtained, so the retest by linking it known denfan results.